Beneficial Effect of Conversion to Belatacept in Kidney-Transplant Patients with a Low Glomerular-Filtration Rate - Belliere, Julie (Hindawi Publishing Corporation, 2014)
Belatacept has been found to be efficient at preserving good kidney function in maintenance kidney-transplant patients. Herein, we report on the use of belatacept as a rescue therapy for two kidney-transplant patients presenting with severe adverse events after treatment with calcineurin inhibitors (CNIs) and mammalian target-of-rapamycin (mTOR) inhibitors. Two kidney-transplant patients developed severely impaired kidney function after receiving CNIs. The use of everolimus was associated with severe angioedema. Belatacept was then successfully used to improve kidney function in both cases, even though estimated glomerular-filtration rate before conversion was <20 mL/min. These case reports show that belatacept can be used as a rescue therapy, even if kidney function is very low in kidney-transplant patients who cannot tolerate CNIs and/or mTOR inhibitors.